Modeling and Analysis of a Micro Gas Turbine Fuelled with Hydrogen and Natural Gas Blends - Barati Shahrokh (EDP Sciences, 2021)
This study deals with implementing an analytical model to simulate the energy performance associated with a Micro Gas Turbine when H2NG (Hydrogen Enriched Natural Gas) blends are used as fuel. The experimental campaign validated the simulation results at the actual operating conditions of the Micro Gas Turbine. The experimental campaign for model validation has been carried out over the spring and summer periods. Additionally, the MGT performance has been detected when fuelled H2NG with hydrogen fraction ranges between 0% vol. to 10% vol., with a 2% vol. Step., according to the main findings, the fuel consumption is reduced significantly. Also, heat recovery and electrical reliability improve slightly even though environmental factors influence the system. A numerical model was developed with MATLAB-Simulink to model the operation of the MGT. Thus, the relative standard errors affecting the main output parameters have been determined.